The Effect of Corticosteroids on the Progression and Outcomes of Polytrauma in Children - Konstantin V. Pshenisnov; Yury S. Aleksandrovich; Andrey S. Lipin (Общая реаниматология, 2024)
Polytrauma in children are among the most common causes of death in the pediatric intensive care unit (ICU).The aim of this study was to evaluate the effect of systemic corticosteroids (SCS) on the progression, laboratory parameters, and outcomes of severe multiple injuries in children requiring ICU.Materials and methods. A retrospective, observational, multicenter (case-control and cross-sectional) study included 203 patients from pediatric ICUs across the Russian Federation. The Abbreviated Injury Scale (AIS) score was 36.81 (25–48), and the Pediatric Trauma Score (PTS) was 5.2 (2–8). SCS were administered to 113 (55.7%) children, 19 (9.36%) of whom died.Results. The most severe changes in laboratory parameters, such as an increase in amylase (35.3 vs. 18.3; P0.001) and activated partial thromboplastin time (APTT) (28.9 vs. 25.8; P0.001), were documented upon admission of children with multiple traumatic injuries to the hospital compared with subsequent days of treatment in the ICU. The average fluid volume (as a percentage of age-related fluid requirements) on the first day of treatment in the ICU was 118.53% and did not exceed 84.42% on subsequent days (P0.001). Higher systolic blood pressure (SBP) during the first three days of ICU treatment was observed in children treated without SCS. SBP tended to decrease by day 5, and then a tendency toward arterial hypertension emerged on days 6–7. In children treated with SCS, blood pressure remained stable during the first seven days in the ICU, contributing to a favorable outcome.Conclusion. The use of SCS in children with severe polytrauma from the first day of ICU treatment contributed to the stabilization of hemodynamic parameters and improved control of shock signs. A positive response to SCS in these patients can be considered a marker for a favorable disease course during ICU treatment.